The health of nations: why inequality is harmful to your health - Kawachi, Ichiro; Kennedy, Bruce P. (New York, 2002)
"The Health of Nations presents evidence from many disciplines that political policies that widen inequalities in income may harm a nation's health. The authors examine a number of indicators of health, such as mortality rates (with respect to which the United States performs miserably in comparison with all the other rich countries), and present arguments to show that one's relative position in society is more important than absolute wealth or income, not only when it comes to general well-being, but in terms of mortality as well. "